The Contours of Contemporary Lithuanian National Identity - Kuznecovienė, Jolanta (Sociologija. Mintis ir veiksmas, 2006)
The article presents the data of the qualitative research (namely focused interview) that was performed by the Centre of Social Anthropology at Vytautas Magnus University in 2005. The aim of the research was to find out what people think are the main features/markers of the Lithuanian national identity and to discover what it means for them to think of themselves as Lithuanians. On the basis of the research data four types of Lithuanian national identity are indicated. Both the main features of the loosing of Lithuanianness as well as possibilities to uphold the Lithuanian national identity for Lithuanian emigrants are described. The article proves the ambivalence of the articulation of Lithuanianness implied by globalization that are followed by changing markers of Lithuanian national identity. The decisive role in the process of identification of Lithuanianness is given not to so called “hard” markers, namely ethnic ones, but rather the markers of emotional dimension.
Keywords: models of identity; national identity; Lithuanianness